2017
DOI: 10.3892/ijo.2017.3997
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of serine/threonine protein phosphatase 5 inhibits tumorigenesis of urinary bladder cancer cells

Abstract: Serine/threonine protein phosphatase 5 (PPP5C) is a member of the protein serine/threonine phosphatase family and has been shown to participate in multiple signaling cascades and tumor progression. We found that PPP5C was highly expressed in bladder cancer tissues compared to normal urothelial tissues, and positively correlated to tumor stages through ONCOMINE microarray data mining. Knockdown of PPP5C via a lentivirus-mediated short hairpin RNA (shRNA) markedly inhibited cell proliferation and colony formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The current standard treatments for MIBC and NMIBC are transurethral resection of bladder tumor (TURBT) and radical cystectomy, respectively, with or without postoperative cisplatin-based combination chemotherapy 47. However, due to high recurrence,8 the cost and curative effect of BCa are still unsatisfactory. Considering early diagnosis and effective treatment, it remains urgent to identify novel cytogenetic molecules for BCa.…”
Section: Introductionmentioning
confidence: 99%
“…The current standard treatments for MIBC and NMIBC are transurethral resection of bladder tumor (TURBT) and radical cystectomy, respectively, with or without postoperative cisplatin-based combination chemotherapy 47. However, due to high recurrence,8 the cost and curative effect of BCa are still unsatisfactory. Considering early diagnosis and effective treatment, it remains urgent to identify novel cytogenetic molecules for BCa.…”
Section: Introductionmentioning
confidence: 99%
“…Then, we conducted GO based on DAVID, which demonstrated that the DEGs were mainly abundant in cell division, mitotic nuclear division, cell proliferation, protein kinase binding and protein serine/threonine kinase activity. Based on these observations, we con rmed their role in BC development (22)(23)(24). Additionally, enrichment of the DEGs in some KEGG pathways, for instance, ECM-receptor interaction and Focal adhesion implicate that they are essential in the pathogenesis of BC.…”
Section: Discussionmentioning
confidence: 62%
“…Researchers have also found that PPP5C, another serine/threonine protein phosphatase, is highly expressed in bladder cancer tissues compared to normal urothelial tissues, which may be related to the mediation of cell proliferation (Chen et al. ). Increases in Et STP may also be related to drug efflux from the cell, which decreases effective intracellular drug concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…showed that knockdown of PPP5C markedly inhibited cell proliferation and colony formation (Chen et al. ). Studies have also shown that PP2A can facilitate virus replication and control ongoing DNA replication (Perl et al.…”
Section: Discussionmentioning
confidence: 99%